A study of oligoclonal band negative multiple sclerosis. Issue 1 (January 1996) - Zeman, A Z; Kidd, D; McLean, B N; Kelly, M A; Francis, D A; Miller, D H; Kendall, B E; Rudge, P; Thompson, E J; McDonald, W I
Abstract : OBJECTIVES--To determine whether oligoclonal band (OCB) negative multiple sclerosis is a reliable diagnosis and, if so, whether it has a distinctive prognosis. METHODS--Retrospective and matched prospective comparison of the clinical and laboratory features of patients with clinical definite multiple sclerosis with and without intrathecal synthesis of oligoclonal IgG. RESULTS--Thirty four patients were identified with apparent OCB negative clinically definite multiple sclerosis. The results of oligoclonal banding proved to have been equivocal in 14 of 34; the clinical diagnosis of multiple sclerosis was questionable in 8 of 34. The remaining 12 patients with "true" OCB negative multiple sclerosis were significantly less disabled than matched OCB positive controls. Re-examination of CSF-serum pairs from six OCB negative patients showed that three remained OCB negative while three showed evidence of intrathecal synthesis of OCBs. CONCLUSIONS--OCB negative clinically definite multiple sclerosis is rare and should be diagnosed with caution; in unequivocal cases it seems to have a relatively benign prognosis.